2015
DOI: 10.1371/journal.pone.0121754
|View full text |Cite
|
Sign up to set email alerts
|

NGF and P75NTR Gene Expression Is Associated with the Hepatic Fibrosis Stage Due to Viral and Non-Viral Causes

Abstract: This study evaluated the relative mRNA expression levels of nerve growth factor (NGF) and the p75 neurothrophin receptor (p75NTR) in different histological stages of human liver disease. Fifty-one liver biopsy specimens obtained from patients with hepatitis B virus (n = 6), hepatitis C virus (n = 28), and non-viral hepatitis – (n = 9) and standard histological liver (n = 8) as controls (CT) were subjected to qPCR and histopathological exams. Our data revealed a significant difference in the NGF expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Previous study from our group has reported the association between the NGF and P75 NRT gene expressions and the liver fibrosis stages due to viral and non-viral causes [ 8 ]. Into this perspective, the present work aims to continue to investigate the factors associated with fibrosis by quantifying expression of the Fas , FasL , and FOXP3 genes in liver biopsy specimens obtained from patients with viral (HBV and HCV) and non-viral hepatic disease (NVHD) chronic hepatitis and correlate their possible roles in the pathogenesis and clinical presentation of these infections and in the various stages of fibrosis and hepatic inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study from our group has reported the association between the NGF and P75 NRT gene expressions and the liver fibrosis stages due to viral and non-viral causes [ 8 ]. Into this perspective, the present work aims to continue to investigate the factors associated with fibrosis by quantifying expression of the Fas , FasL , and FOXP3 genes in liver biopsy specimens obtained from patients with viral (HBV and HCV) and non-viral hepatic disease (NVHD) chronic hepatitis and correlate their possible roles in the pathogenesis and clinical presentation of these infections and in the various stages of fibrosis and hepatic inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…The paracrine loop between the neurotrophins produced by hepatocytes and the p75 NTR receptor expressed in HSCs, which, on the one hand, stimulates hepatocyte proliferation and, on the other hand, blocks and regulates this phenomenon (Amoras et al, 2015), was not the concept adopted in the present study. Based on the evaluation of polymorphic variants well established in the literature, we suggest that NGF has a regulatory role in maintenance of hepatocyte integrity, leading to reducing liver enzyme levels and increase of the viral load.…”
Section: Discussionmentioning
confidence: 94%
“…NGF and p75 NTR are naturally expressed in healthy liver tissue and under conditions of tissue damage (Passino et al, 2007), and their physiological roles are related to inflammation and the progression of liver fibrosis (Amoras et al, 2015). Thus, it is important to evaluate the influence of genetic variations on these factors as aspects linked to the evolution of liver damage in patients with liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations